Conceptualising the Romantic Relationship - Jana Baćević (University of Belgrade, 2016)
This paper approaches the phenomenon of the "romantic relationship" as understood within some of the most prominent paradigms in the social sciences. These interpretative frameworks are then applied to the model of the romantic relationship acquired during my own research on the concepts of romantic relationships among young professionals in Belgrade, Serbia. I argue that none of the presented frameworks can be solely relied upon to explain the phenomenon, but that in combination they do offer very valuable insights. This represents an example of how the application of different paradigms in social sciences can help to clarify the nature of a phenomenon, rather than representing a ground for contestation.